A Study on Female Image Alienation Translation in Chinese Classical Literature Based on Computer Corpus. Issue 2 (May 2021) - Bi, Yanyan; Zhang, Deyu
Abstract: In the five thousand years of Chinese history, there are numerous classic literature works. Even in the past, when women were the vassals of men, there is still no lack of outstanding women who remain famous in history and become regular visitors in various literary works. But with the advent of economic globalization, cultural output also become a part of the communication of civilization, there is no denying that many foreigners to China still have a misunderstanding, the translation of Chinese women literature image more easily moving heart, able to produce lasting to foreign audiences and subtle role, affecting people abroad for China's views and cognition. Based on this, this paper explores the translation of female image alienation in Chinese classic literature based on computer corpus.